2019
DOI: 10.1088/1361-665x/aaf32b
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on rheological properties of lithium-based magnetorheological grease

Abstract: This paper investigates the impact of temperature on the rheological properties of magnetorheological (MR) grease containing carbonyl iron suspended in lithium-based grease within the temperature range from 10℃ to 70℃under influence of temperature, i.e. from 10℃ to 70℃. Lithium-based MR grease with 70% weight fraction of carbonyl iron has beenis firstly prepared by mechanical mixing. The apparent viscosity and shear stress as a function of shear rate under different temperatures and magnetic field strengths ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 47 publications
1
46
1
Order By: Relevance
“…It can be concluded that the ability of energy storage for PU matrix decreases with the increase of shear strain amplitude. With the influence of the magnetic flux density, as can be seen in Figures 6B-E, MR gels exhibit obvious linear viscoelastic region at the small strain range, which was the same as the dynamic properties of MR grease (Wang et al, 2019). It should be noted that the data is plotted with logarithmic horizontal axis to clear present the linear region.…”
Section: Rheological Properties Under Oscillatory Shearsupporting
confidence: 58%
“…It can be concluded that the ability of energy storage for PU matrix decreases with the increase of shear strain amplitude. With the influence of the magnetic flux density, as can be seen in Figures 6B-E, MR gels exhibit obvious linear viscoelastic region at the small strain range, which was the same as the dynamic properties of MR grease (Wang et al, 2019). It should be noted that the data is plotted with logarithmic horizontal axis to clear present the linear region.…”
Section: Rheological Properties Under Oscillatory Shearsupporting
confidence: 58%
“…10(a) that the inuence of magnetic elds on the storage modulus of MRG shows a decreasing trend with increasing of magnetic elds, resulting from the gradually saturated magnetic particles in MRG. 34 Therefore, the gaps between the steady-state value of storage modulus decrease progressively with the increasing of magnetic elds. 35 On the other hand, taking MRG-40 for example, storage modulus appears a rising trend with the enlargement of frequency at rst and then gets a plateau gradually.…”
Section: Frequency Sweepmentioning
confidence: 97%
“…viscosity, yield stress, storage modulus and loss modulus. [11][12][13][14][15][16] The normal force of the MR materials is the force induced by the forming of chain or cluster structure along the direction of the magnetic eld which is perpendicular to the shear stress. This normal force has signicant impacts on the mechanical performance of MR materials-based devices and is suggested to be considered in the design stage of MR devices.…”
Section: Introductionmentioning
confidence: 99%